(untitled) (Journal of Nepal Geological Society, 2011)
Plant macrofossil investigation was carried out on the Late Quaternary sediments of the Kathmandu Valley, central Nepal. The fluvial-deltaic to fluvio-lacustrine deposits of the Kathmandu Basin are found to be rich in plant macrofossil assemblages. A total of 66tax.a from 38 families were identified to genus and some of them up to species level from five different macrofossil bearing layers (BG- I Lo BG-5) from the 33 m thick Besigaon section belonging to the Gokarna Formation exposed at the northern part of the basin. The lower half of the exposed section is completely devoid of macrofossil horizons, however the upper half yielded a significant amount which could be used for climatic interpretation. The characteristic feature of the Besigaon section is the dominance of angiosperms in the lower and middle horizons (BG-I, BG-2, BG-3) but gymnosperms in the upper horizons (BG-4, BG-5). The dominance of angiosperms such as Carpinus, Alnus, Pyracantha, Quercus subgen. Cyclobalanopsis, Eurya and Zizyphus suggest the deposition of the lower and middle horizons in warm temperate climatic condition. The humid phase is documented during deposition of the BG-3 and BG-4 horizons with the findings of Selaginella remotifolia and wetland aquatic taxa such Carex, Schoenoplectus, Nymphoides indica. In contrast, the upper horizons dominated by gymnosperms such as Abies, Pinus, Picea smithiana, Tsuga dumosa and Taxus wallichiana represent cold and humid climate. The macrofossils from Besigaon section suggest minor fluctuation in climate from wam1to cold temperate phase with increasing humidity during the Late Pleistocene.